Use of mobile phones to collect data on COVID-19: phone access and participation rates, in Rakai, Uganda - Robert Ssekubugu; Anthony Ndyanabo; Fredrick Makumbi; Anna Mia Ekström; Laura Beres; Grace Nalwoga Kigozi; Hadijja Nakawooya; Joseph Ssekasanvu; Maria J Wawer; Fred Nalugoda; Nelson Sewankambo; Victor Ssempijja; et al. (Global Health Action)
During the COVID-19 pandemic lockdown, we deployed a rapid, mobile phone-based survey to assess access and participation rates when using mobile phones to collect data on COVID-19 in Rakai, south-central Uganda. We sampled prior Rakai Community Cohort Study (RCCS) participants based on HIV status using mobile phone contacts. We administered a 30-minute phone-based interview to consenting participants to assess their knowledge about different aspects of COVID-19 and their access to care. Our analysis compares the mobile phone survey participation rates with historic participation rates in regular RCCS face-to-face interviews. We supplemented phone survey data with demographic, behavioral, and HIV status data from prior face-to-face RCCS surveys. Phone access in Round 19 of the RCCS was found to be 90.2%, with lower access among older people, and people living with HIV. When including only individuals who participated in the previous RCCS survey round, participation in the face-to-face survey (81.9%) was higher than participation in our phone survey (74.8%, p < .001). Survey participation was higher among people living with HIV compared to HIV-negative individuals (84.0% vs 81.4%, p < .001) in the face-to-face survey, but in the phone survey the reverse was found, with participation rates being higher among HIV-negative individuals compared to people living with HIV (78.0% vs 71.6%, p < .001). It was possible to collect data from an existing population cohort during the lockdown using phones. Phone access was high. Overall participation rates were somewhat lower in the phone survey, notably in people living with HIV, compared to the face-to-face survey.